Pengaruh Potongan Harga dan Penataan Produk terhadap Keputusan Pembelian Konsumen di Matahari Departemen Store Pekalongan (Studi Kasus Produk Cardinal Shoes Ladies) - Rizka Ariyanti; M. Iqbal Notoatmojo; Aria Mulyapradana; Putri S. (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2021)
This study aims to examine and analyse the effect of price cuts, product arrangement on purchasing decisions on consumer purchasing decisions at Matahari Department Store Pekalongan, especially Cardinal Shoes Ladies.To test these variables, the researcher used 100 consumer respondents in the Matahari Department Store Pekalongan. The type of research used is explanatory research. Data collection techniques using interview techniques and questionnaires. The type of data used in this study is primary data. Furthermore, the data that has been collected is analysed quantitatively using multiple regression using the SPSS program. The results of the research simultaneously show that the variable price discount has an effect on purchasing decisions, the variable of product arrangement has an effect on purchasing decisions, while for the partial research results, the variables of Price Discounts and Product Charges affect p urchasing decisions. Keynote: Price discount, product arrangement, purchasing decisions